Moral sensitivity as a personal and work attribute of emergency care nurses: a cross-sectional study - Mariana Oliveira Antunes Ferraz; Carlise Rigon Dalla Nora; Maria Manuela Ferreira Pereira da Silva Martins; Rosinete Souza Barata; Larissa Dantas Ferreira; Darci de Oliveira Santa Rosa (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the moral sensitivity of Brazilian emergency care nurses according to their personal and work characteristics. Method: this is a quantitative, descriptive, cross-sectional study with a convenience sample. A total of 422 nurses from emergency care services in the five regions of Brazil took part. Sociodemographic and work-related information was collected, as well as the Brazilian version of the Moral Sensitivity Questionnaire. After approval by the Research Ethics Committee, the data was collected using a self-administered form on the Google Forms Platform, organized using Excel software and analyzed using the R language. Results: nurses with longer experience in emergency care services showed higher levels in the interpersonal orientation, moral conflict and moral significance dimensions, while in the professional knowledge dimension, men showed higher levels, as evidenced by items that include confidence in nursing knowledge, intuition, experience and opinion. Conclusion: the differences in the nurses' moral sensitivity were due to their professional experience. It should be emphasized that valuing the sharing of intergenerational experiences in service could be a possible strategy for fostering moral competencies in the field of practice.